2003
DOI: 10.1021/jp022092f
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Isolation Fourier Transform Infrared Spectroscopic and Density Functional Theoretical Studies of the Reactions of Chromium Atoms and Acetylene

Abstract: The reactions between chromium atoms and acetylene have been investigated in solid argon with infrared absorption spectroscopy. It is found that the ground-state chromium atoms reacted with acetylene to form the metallocyclopropene Cr(C2H2) molecule spontaneously on annealing. The Cr(C2H2) molecule underwent photochemical rearrangement to the alkynyl hydride HCrCCH molecule upon ultraviolet−visible irradiation. The two products were identified on the basis of isotopic IR studies with 13C2H2 and C2D2, and densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 42 publications
8
52
0
Order By: Relevance
“…176 The reactions between Cr atoms and acetylene have been explored. 177 Ground state Cr atoms react with acetylene in Ar matrices to form the metallocyclopropane molecule Cr(C 2 H 2 ) spontaneously on annealing. Photolysis of this cyclic species affords the alkynyl hydride HCrCCH.…”
Section: Groups 15 16 and 17mentioning
confidence: 99%
“…176 The reactions between Cr atoms and acetylene have been explored. 177 Ground state Cr atoms react with acetylene in Ar matrices to form the metallocyclopropane molecule Cr(C 2 H 2 ) spontaneously on annealing. Photolysis of this cyclic species affords the alkynyl hydride HCrCCH.…”
Section: Groups 15 16 and 17mentioning
confidence: 99%
“…Therefore, the interactions of transition metals with the typical and simplest unsaturated hydrocarbons like acetylene have received considerable attention from both experimental and theoretical points of view. Four kinds of transition metal–acetylene complexes have been addressed via the reactions of transition metals with acetylene, including the side-on M-(η 2 -C 2 H 2 ), the vinyl M–C 2 H 2 , the inserted HM–CCH, and the vinylidene MCCH 2 . Zhou and co-wokers found that the ground-state Cr atoms reacted with acetylene to form metallocylcopropene, which will rearrange into the inserted product upon ultraviolet–visible irradiation . Recently, using matrix isolation infrared spectroscopy and density functional theory (DFT) calculations, Andrews and co-workers have reported that the reactions of laser-ablated transition metals (Sc, Y, La, Cr, Mo, W) with acetylene produce the π and the inserted complexes. , Xu and co-workers have identified the products of the side-on M-(η 2 -C 2 H 2 ) (M = Y, Ge, Sn), the inserted HYCCH (M = Y, Ge, Sn, Pb), anionic HScCCH – , HScScCCH – , and the vinylidene Sn 2 CCH 2 . , Duncan and co-workers investigated the cationic M + (C 2 H 2 ) complexes (M = Ca, V, Fe, Co, and Ni) by using infrared photodissociation spectroscopy and theoretical calculations. Ramsvik et al studied the chemisorption and decomposition of acetylene on the Co single-crystal surface using the near-edge X-ray absorption fine structure (NEXAFS) technique and observed that the dehydrogenated fragment C 2 H was adsorbed on the Co crystal surface in the temperature range of 200–300 K.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9]11 On the basis of the C−C bond lengths and observed stretching frequencies, the Group 4 metals form remarkably strong π complexes due to effective back-donations to the π* orbitals in M-η 2 -(C 2 H 2 ). 4 Group 3 and 5 metals also generate strong π complexes but slightly weaker than the Group 4 metal analogues. 4 In contrast, the main group and late transition metals produce much weaker π complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Huang et al have recently reported the observation of the two and three vibration bands of the Cr π and insertion complexes in reaction with acetylene. 4 In this article, we report reactions of Group 6 metals with C 2 H 2 and their products identified in the matrix IR spectra. The backdonation to the π system continuously decreases from the Group 4 to 6 metal systems; the absence of the vinylidene products is consistent with the high activation energies, and the insertion complexes have bent structures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation